Pengaruh Basis Salep Terhadap Sifat Fisik Sediaan Salep Ekstrak Etanolik Bonggol Pisang Ambon (Musa Paradisiaca Var. Sapientum L.) Sebagai Penyembuhan Luka Terbuka Pada Tikus - Fatimah, Yuliana, Gunawan Setiyadi, M.Sc., Apt (2017)
The content of ambon banana weevil in the form of flavonoids, saponins and tannins play a role in the healing process of open wounds. The purpose of this research is to analyze the effect of variations base ointment in the physical properties and healing open wounds. Extraction of ambon banana weevil done soxhletation with 96% ethanol. Banana weevil is presented in the form of an ointment with four different bases are water-soluble base, base leached, base absorption, and a hydrocarbon base. Observation of physical properties of an ointment include organoleptic, homogeneity, pH, viscosity, adhesion, and dispersive power for 4 weeks. Wound healing power tests using male rats as many as 27 rats were injured her back with a diameter of ± 1.5 cm. The wounds were applied with ointment tested and wound diameter was measured from the first day until cured. The results showed variations affect the ointment base color, viscosity, dispersive power, and adhesion, but has no effect on homogeneity, and pH. Variations ointment base also affects the healing of open wounds. Ambon banana weevil ointment base and a water-soluble hydrocarbons provides an open wound healing effect more quickly followed by banana weevil ambon ointment base absorption and leached.